Role of acute physiology and chronic health evaluation II scoring system in risk stratification and management of small bowel perforations - Kumar, Sanjana; Arora, Jainendra K.; Jain, Sunil Kumar (International Surgery Journal, 2020)
Background: Despite the surgical treatment, sophisticated intensive care units, latest generation antibiotics and a better understanding of pathophysiology, the morbidity and mortality rate of perforation peritonitis are still high. Patients are usually managed by subjective decision of surgeon based on which mortality is very high. Methods: This was a double-blind observational study conducted over a period of 18 months on 50 patients with small bowel perforations. Based on the acute physiology and chronic health evaluation (APACHE) II score at presentation, patients were triaged into 3 groups: group 1 (score ≤10), group 2 (score 11 to 20) and group 3 (score >20). Study population was managed by the subjective decision of the operating surgeon who was blinded off the APACHE II score of patients. Hence removing the possibility of bias and observing a correlation between surgical outcome and APACHE II score of the patient. Results: Patients with higher APACHE II score (>10) were more likely to undergo exteriorization of bowel. Length of hospital stay was also found to be increased with an increase in score. APACHE II score of 10 was found to predict mortality with significant difference between 2 groups. Below this score the mortality was 0% and above this score the mortality rate rose to 31.25%. Conclusions: APACHE II can be used as a reliable and uniform scoring system as its assessment at presentation in patients of small bowel perforations provides an insight to their surgical management as well as predicting overall outcome.